2019
DOI: 10.1128/aem.01369-19
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Abundances ofMethanobacterialesandSyntrophobacteralesMay Help To Prevent Corrosion of Metal Sheet Piles

Abstract: Iron sheet piles are widely used in flood protection, dike construction, and river bank reinforcement. Their corrosion leads to gradual deterioration and often makes replacement necessary. Natural deposit layers on these sheet piles can prevent degradation and significantly increase their life span. However, little is known about the mechanisms of natural protective layer formation. Here, we studied the microbially diverse populations of corrosion-protective deposit layers on iron sheet piles at the Gouderak p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 112 publications
0
14
0
Order By: Relevance
“…Members of the M. maripaludis such as KA1 and OS7 are capable of secreting extracellular hydrogenases that transfers electrons from the metal surface to form hydrogen for methanogenesis. However, it is known that Methanobacterium IM1 have higher affinity for elemental iron than for H 2 (Beese-Vasbender et al, 2015;Kip et al, 2017;in 't Zandt et al, 2019). Though the specific mechanisms are still under investigation, it was speculated that Methanobacterium IM1 can tightly adhere to the metal surface, allowing cell-surface redox mediators to effectively transfer electrons (Beese-Vasbender et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Members of the M. maripaludis such as KA1 and OS7 are capable of secreting extracellular hydrogenases that transfers electrons from the metal surface to form hydrogen for methanogenesis. However, it is known that Methanobacterium IM1 have higher affinity for elemental iron than for H 2 (Beese-Vasbender et al, 2015;Kip et al, 2017;in 't Zandt et al, 2019). Though the specific mechanisms are still under investigation, it was speculated that Methanobacterium IM1 can tightly adhere to the metal surface, allowing cell-surface redox mediators to effectively transfer electrons (Beese-Vasbender et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Periodic sulfide measurements were conducted by collecting samples from individual sections of the column (Figure 1). At the end of the experiment, columns were taken apart by section and cleaned using NACE protocol SP0775-2013 (Haroon et al, 2013;Pinnock et al, 2018). Beads were weighed before and after the experiment by section using a Sartorius analytical scale (Sartorius AG, Germany) to calculate the individual corrosion rate (CR).…”
Section: Multiport Flow-column Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…With these results we expand the diversity of microbial interactions on Fe 0 between acetogens and methanogens (from competition (Palacios et al, 2019b) to opportunism (this study)). Some studied suggested that methanogens like Methanothermobacter may have a protective role during corrosion (in 't Zandt et al, 2019), however here we show how such methanogens are positively affected by acetogenic partners. In consequence we recommend that the corrosive effects of methanogens should be investigated not only in pure culture but also in consortia with bacterial partners before suggesting they have a protective anticorrosive role.…”
mentioning
confidence: 43%
“…But it is unknown whether any of these species can act as autotrophic acetogens, which is the only possibility in this enrichment. Of these, some Bacillus induced corrosion under nitrate reducing conditions (Wan et al, 2018;Xu et al, 2013), but in other instances Bacillus species inhibited corrosion by forming a passivating film of extracellular polymeric substances and/or calcite (Guo et al, 2019;. Corrosion was also inhibited by a Desulfitobacterium that oxidized Fe(III)-minerals to vivanite, forming a protective passivating layer on the metal surface (Comensoli et al, 2017).…”
Section: Acetogensmentioning
confidence: 99%